Challenges to Levelling Up: Post-COVID precarity in “left behind” Stoke-on-Trent - Etherington, David; Jones, Martin; Telford, Luke (Frontiers in Political Science, 2022)
The COVID-19 pandemic both revealed and intensified the United Kingdom's (UK) regional inequalities. The UK is widely recognised as one of the most regionally unbalanced nations in the developed world, with many “left behind” places across the North and Midlands like Stoke-on-Trent falling way behind parts of London and the Southeast of England in terms of living standards in the neoliberal era. Since 2019 the UK Government have promised to “Level Up” the UK, culminating in the publication of the Levelling Up White Paper in 2022. This pinpointed the need to raise living standards, opportunity, and prosperity across the UK, with Stoke identified as a priority area. Primarily utilising qualitative case study data (N = 15) provided by Citizens Advice Staffordshire North and Stoke-on-Trent (CASNS), this article explicates how there are myriad challenges to the Levelling Up strategy in Stoke. Suffering from a historical legacy of the loss of its ceramics and manufacturing industries, the paper outlines how the city-region contains a structural cocktail of disadvantage including low paid jobs, welfare erosion, indebtedness, destitution, and food insecurity. The article closes by discussing the implications of these structural problems for the Government's Levelling Up agenda, suggesting that only a transformative shift in both allocated resources and neoliberal spatial development will regional imbalances be adequately addressed in places like Stoke-on-Trent.